2016
DOI: 10.2298/vsp140911141h
|View full text |Cite
|
Sign up to set email alerts
|

Therapist’s interpersonal style and therapy benefit as the determinants of personality self-reports in clients

Abstract: The results of this study indicate the importance of further research on therapist's interpersonal style, as well as further validation of the instrument that measures this construct. Besides, a client's perception that the therapy is being helpful could instigate more explorative and approach-oriented behavior, what indirectly might contribute to a client's stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In times of great insecurity and unsafety, having too much autonomy could presumably be associated with a loss of structure. For example, as a therapist style, supportive autonomy was found to predict personality plasticity indirectly through the perception of a therapy benefit (Hadžiahmetović et al, 2016). This finding shows that the perception of contextual usefulness may mediate how autonomy-supportive style contributes to behavioural flexibility.…”
Section: Self-determined Learning In the Constructivist Pandemic-indu...mentioning
confidence: 80%
“…In times of great insecurity and unsafety, having too much autonomy could presumably be associated with a loss of structure. For example, as a therapist style, supportive autonomy was found to predict personality plasticity indirectly through the perception of a therapy benefit (Hadžiahmetović et al, 2016). This finding shows that the perception of contextual usefulness may mediate how autonomy-supportive style contributes to behavioural flexibility.…”
Section: Self-determined Learning In the Constructivist Pandemic-indu...mentioning
confidence: 80%
“…Also, studies have shown that interpersonal personalities can be associated with health outcomes, 63 parenting styles, 64 and the perception of therapy benefit. 65 This versatile tool may be promising not only in the field of recovering social function of PLWH but also for many other unexplored domains in China. With the findings from our research, the Chinese version of IPIP-IPC could be employed for assessing interpersonal personalities among PLWH in China with evidence.…”
Section: Discussionmentioning
confidence: 99%